Effects of nitrate and sulfate on greenhouse gas emission potentials from microform-derived peats of a boreal peatland: A 13C tracer study. (September 2016) - Lozanovska, Ivana; Kuzyakov, Yakov; Krohn, Johannes; Parvin, Shahnaj; Dorodnikov, Maxim
Abstract: Increasing natural and anthropogenic deposition of nitrate (NO3 − ) and sulfate (SO4 2− ) to peatlands may modify CH4 oxidation, CO2 and N2 O production, thereby affecting the balance of greenhouse gases (GHG) globally. Among environmental factors controlling these biogeochemical processes, effects of peatland microrelief are poorly understood. Fluxes of CO2, CH4 and N2 O were measured before and after incubation with NO3 − and SO4 2− for peat samples collected from various microrelief positions of a boreal oligotrophic mire in Eastern Finland. Soil was spiked with 13 CH4 to understand the processes of CH4 oxidation, its microbial utilization and incorporation into soil organic matter (SOM). We hypothesized that the addition of NO3 − and SO4 2− would 1) stimulate CO2 and N2 O production (nutritional effect), but 2) decrease CH4 oxidation due to acceleration of other more energetically favorable processes (e.g. denitrification), and 3) these patterns should follow the naturally established aerobic zone of a microform type and decrease with depth. Microbial biomass (MB) at 50 cm below all microforms was 9–15 folds higher than in the topsoil. MB controlled the GHG dynamics and was related to specific depth-dependent environmental conditions, rather than oxygen availability. Indeed, production of CO2 and N2 O, and oxidation potentials of CH4 revealed no clear linkage with the naturally established aeration zone of the peatland's microforms. Following NO3 − and SO4 2 − addition, production of CO2 decreased by 20–65% compared to the control, with the greatest reduction in CO2 emission occurring in the topsoil of hollows. In turn, CH4 oxidation was suppressed by 20–94% with NO3 − addition at 50 cm in lawns and with both NO3 − and SO4 2− at 50 cm in hollows. The N2 O production was increased up to 180–240 times under NO3 − treatment at 50 cm in hollows and lawns. In conclusion, human-induced deposition of NO3 − and SO4 2− may suppress CO2 emissions from and CH4 oxidation by boreal oligotrophic mires especially under the conditions of deposition increase. Finally, the deposition of inorganic compounds is strongly important to be considered in the estimation of ecosystem C and N balances. Graphical abstract: Highlights: Maximum CO2 production and CH4 oxidation corresponded to the highest MBC content at 50 cm depth. Lowest methanotrophic potential of the topsoil was detected in hummocks. CO2 production was suppressed by 20–65% in the presence of added NO3 − and SO4 2− . CH4 oxidation was suppressed by 20–94% after amendment with NO3 − and SO4 2− . Addition of NO3 − increased N2 O production by 180–240 times at 50 cm in hollows and lawns.